'Efficiency' and 'Vocationalism' as Structuring Principles of Industrial Education in the USA - Gonon, Philipp [Verfasser] (My University, 2009)
"The aim of this paper, based on a comparative viewpoint from an European outsider perspective, is to present a brief historical reconstruction of the pedagogical and educational political discussion about education for the industrial sector in America. The discussion was triggered by the emerging idea that one of the principal tasks of education should be to prepare youth most effectively for their upcoming work life. It followed that the constitution and role of the American schools to achieve this purpose were widely debated early in the twentieth century by eminent pedagogues. Some of these pedagogues argued for an American education system that also developed vocational abilities and skills, whereas others favoured only the development of general knowledge. During the course of this dispute, across the first half of the twentieth century, other key issues were brought forward such as whether this much vaunted vocational education should be enacted in comprehensive schools or whether other kinds of schools should be established for these purposes. Furthermore, another model that resembled the German vocational system was also proposed through this period. However, ultimately and unlike in Germany, a dual model of vocational education and training characterised by an interlocking of school-based instruction and workplace training has not managed to establish itself as a discrete educational sector in America. Currently, education for industry is provided mainly in schools and tends to be oriented towards the criteria of efficiency and vocationalism." (Autorenreferat, BIBB-Doku)
Keywords: T 2.1 Bildungstheorien; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.3.2 Nordamerika; Berufsbildung; Bildungstheorie; Beruflichkeit; Allgemeinbildung; Effizienz; Industrie; USA